KINERJA DAN PROSPEK PEMASARAN KOMODITAS MANGGA (Studi kasus petani mangga di Propinsi Jawa Barat) - SUPRIATNA, ADE (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 1 Februari 2008, 2012)
This study was conducted in 2005 and took place in West Java. The objectives of study were (a) to identify characteristics of farmers and mango cultivation practice, (b) to analyze the economical visibility of mango farm, (c) to describe the marketing channels and the manner of each institution, and (d) to analyze the marketing margin and farmers share. The results showed that based on partial analysis, mango farm spent cost of Rp.6.4 million, gave farm return of Rp.30.1 million and farm benefit of Rp.23.6 million per hectare per year. The mango farm was suitable economically with R/C ratio of 4.64. In farm level, mango was classified into two grades, namely grade A/B (70%) and non grade (30%) which was named grade C (rucahan). For West Java area, grade A/B was marketed through three channels, namely (1) farmer ? collection trader ? agent ? central market ? traditional market ? consumer, (2) farmer ? collection trader ? agent ? central market ? shop/mangostand ? consumer, (3) farmer ? collection trader ? agent ? central market ? supplier ? super market ? consumer. While non grade (C) was marketed through one channel, namely farmer ? collection trader ? agent ? local traditional market ? consumer. The farmers faced a structure of imperfect competitive market with some indicators such as a lot of seller and a little of buyer, farmer’s marketing information was low, and the mango price was determined by buyer. The central market took place as a referee market; the mango price offered by central market would be an arithmetical standard to determine the purchasing price by formerly institutions until the farmer level. In marketing grade A/B, agent reached a highest margin, namely Rp.2, 500,-. They spent a highest cost of marketing and took a higher risk caused by fluctuation of price. The third channel was longest channel and took a farmers share of 29.4 percent. While the first and second channels were shorter than that of the third one and they took the farmers share of 41, 7 and 40.0 percent, respectively.
Keywords: Performance, Mango, Marketing, West Java.